Playing Victim dan Manipulasi Kebenaran: Analisis Teologis dalam Pembacaan Reflektif Kejadian 3:1-24 - Andreas Sese Sunarko; Yonatan Alex Arifianto (Jurnal Teologi Gracia Deo, 2023)
Playing victim behavior is the action of those who blame themselves on others and position themselves as victims. This contradictory sense of responsibility is widespread in everyday life. Therefore, this article aims to provide a new understanding and paradigm regarding playing victims that contradicts God's truth.Using descriptive qualitative methods, it can be concluded that playing victims in manipulating the truth is a theological reflection in reading Genesis 3:1-24; first, Christianity must understand the nature of playing victims and its impacts. Genesis 3:1-24 shows how humans blame others or circumstances to avoid responsibility for their mistakes. This also emphasizes the importance of playing the victim in theological ethics and Christian faith. Theological reflection, humility, and an attitude of responsibility in honesty through recognizing mistakes and confessing sins are not to play the victim. Jesus also taught us to live in love. Furthermore, in a theological reflective context, it helps identify the role of the Garden of Eden story and the issue of truth manipulation in the "playing victim" attitude that is actualized in human life. Therefore, the role of Christianity in the actualization of life without suffering victims becomes a role that is responsible for personal actions and decisions to live in honesty and responsibility and dare to admit mistakes.  AbstrakPerilaku playing victim merupakan tindakan merekayang melemparkan kesalahannya kepada orang lain dan memosisikan dirinya sebagai korban. Hal yang bertolak belakang akan rasa bertanggung jawab ini marak di lingkungan kehidupan sehari-hari. Oleh karena itu, artikel ini bertujuan untuk memberikan pemahaman dan paradigam baru terkait playing victim yang tidak sejalan dengan kebenaran Allah. Menggunakan metode kualitatif deskritif maka dapat disimpulkan bahwa playing victim dalam manipulasi kebenaran: reflektif teologis dalam pembacaan kejadian 3:1-24, pertama keristenan harus memahami hakikat playing victim dan dampaknya. Sebab dalam Kejadian 3:1-24 memperlihatkan bagaimana manusia  cenderung untuk menyalahkan orang lain atau keadaan sebagai upaya untuk menghindari tanggung jawab atas kesalahan mereka. Maka hal ini juga menekankan pentingnya playing victim dalam etis teologis dan iman Kristen. Di mana refleksi teologis dan kerendahan hati serta sikap dalam bertanggung jawan dalam kejujuran melalui pengenalan kesalahan dan pengakuan atas dosa untuk tidak playing victim. Juga diajarkan Yesus untuk hidup dalam kasih. Selanjutnya dalam konteks reflektif teologis membantu mengidentifikasi peran kisah taman eden dan persoalan manipulasi kebenaran dalam sikap "playing victim" yang diaktualisasikan dalam kehidupan manusia. Oleh karena itu peran kekristenan dalam aktualisasi hidup tanpa palying victim menjadi peran yang bertanggung jawab atas tindakan dan keputusan pribadi untuk hidup dalam kejujuran dan tanggung jawab yang berani mengakui kesalahan.